Genetic characterization studies of F population of Indian mustard × East- 2 European mustard through principal component analysis - Tushadri Singh; SK Gupta; Akriti Sharma; Ashish Sheera; Babita Bhatt (Journal of Oilseed Brassica, 2026)
The study was conducted during the Rabi season of 2019-20, focused on the principal component analysis (PCA) of F 2generation resulting from a cross between Indian mustard and East European mustard. The F population, comprising 2359 plants, was systematically evaluated for agromorphological traits, and PCA revealed three principal componentaxes, collectively explaining 71.45% of the total variation. Notably, the first component (PC1) primarily featured plantmorphological and seed yield-contributing traits, contributing maximum variability (42.70%) while PC2 contributedfor 14.43% of total variability and PC3 14.32% of total variability. Additionally, subsequent principal componentshighlighted specific trait contributions, demonstrating the potential for effective selection in crop breeding programs.The study underscores the importance of employing PCA to evaluate genetic diversity and discerns the primecontributors to variability in Indian mustard, providing valuable insights for crop breeding programs.